The idiot - Dostoyevsky, Fyodor, 1821-1881 (Vintage classics., 2003)
Twenty-six-year-old Prince Lev Nikolayevich Myshkin returns to Russia after spending several years at a Swiss sanatorium. Scorned by the society of St. Petersburgh for his idiocy, generosity and innocence, he finds himself at the centre of a struggle between a beautiful kept woman and a gorgeous, virtuous girl, both of whom win his affection. Unfortunately, Myshkin's very goodness seems to precipitate disaster, leaving the impression that, in a world obsessed with money, power, and sexual conquest, a sanatorium may be the only place for a saint. --wikipedia.com.